Tribological Evaluation of Turbostratic 2D Graphite as Oil Additive - Halley Welther Jacques Dias (Lubricants, 2021)
In this study, powder technology was used to obtain Fe-SiC composites in which SiC particles act as precursors to generate a large amount of turbostratic graphite dispersed in the composite matrix. The selection of the alloy composition was studied employing Thermo-Calc® software to obtain the temperature and composition range for the stabilization of the graphite phase in iron with a high yield. The extracted turbostratic 2D graphite particles were dispersed in mineral oil in order to evaluate the potential of these particles as a lubricating oil additive. The structure and morphology of the extracted graphite were examined by Raman spectroscopy and transmission electron microscopy (TEM), indicating the highly disordered nature of turbostratic graphite. Reductions in the friction coefficient and wear rate of a tribological pair were observed when compared to the pure mineral oil and mineral oil with commercial graphite particles added. The misorientation and increase in interplanar distances of turbostratic 2D graphite induce a low degree of interaction between these atomic planes, which contributes to the low-friction coefficient and the lower wear rate obtained for this system.